ANALISIS TINGKAT PELAYANAN (LEVEL OF SERVICE) PADA RUAS JALAN LUAR KOTA: Studi Kasus Jalan Raya Singaparna Kabupaten Tasikmalaya Km. Bdg. 205+000 - Km. Bdg. 206+000 - Herman Sudrajat, Giri; Saepudin, Uu; Martha, Taufik (Jurnal Ilmiah Teknik Sipil, 2026)
Roads as the main infrastructure play an important role in supporting regional economic mobility and growth. However, an increase in the number of motor vehicles often leads to congestion and traffic congestion, which is not only caused by vehicle volume or road capacity, but also by disorderly rider behavior, such as ignoring signs, cutting lanes, and parking carelessly. The Singaparna Road section in Tasikmalaya Regency, which is the connecting artery between Garut Regency and Tasikmalaya Regency, often experiences congestion due to high traffic volume and side obstacles. So this study aims to analyze traffic volume, side obstacles, free flow speed, road section capacity, and degree of saturation, as well as determine the level of service on Singaparna road, Tasikmalaya Regency, Km. Bdg. 205 + 000 – Km. Bdg. 206 + 000. The method used in this study is a survey, by conducting direct observations at the research location to obtain data that is a reference in conducting an analysis using PKJI 2023. The results of the study showed that the peak traffic volume on Jalan Raya Singaparna, Tasikmalaya Regency occurred on Saturday at 16.00 - 17.00 of 3042 smp/hour. The frequency of the weight of side obstacles including the category of high resistance occurred on Monday 14 July 2025 at 06.00 - 07.00 amounting to 1397 with an average weight frequency of 349, the free flow speed was obtained at 52.73 km/h for passenger cars, then the capacity of the road section was obtained 3302.21 smp/hour, and the degree of saturation was known to be 0.92. 2. So the level of service (Level of Service) at peak hours on Saturday at 16.00 - 17.00 is 3042 smp/hour, then the Singaparna road in Tasikmalaya Regency is at level E with alternative improvements to level C with obstacles that can be solved and become very low and the direction separation factor can be optimized.